The brood sow - Fields, James William (My University, 1903)
Introduction: FEEDING. --The little sow should not be allowed to stop growing after weaning but to the contrary, should be made to grow as rapidly as possible all the time. She should not be kept fat but in good flesh, nor should she be fed concentrates but to the opposite she should have a bulky food which will keep her digestive tract distended making her capable of handling a great amount of food when she gets to be a year old. Clover or alfalfa pasture in the summer and wheat or rye pasture in winter should be provided for the brood sow all their lives. Clover and alfalfa hay are relished in the winter. About an acre per sow would be the right amount of pasture. A very desirable grain is oats or a mixture of oats and corn ground up together make an excellent feed for young sows. Some bran and shorts mixed in the slop is very good. This keeps the young sow growing well and the slop gives bulk as does the pasture. It is poor policy to put the young sow you intend for breeding purposes in the fattening pen with the hogs intended for market. This makes her lazy and reduces her power to convert food consumed into feed for the fetus and little pigs as she has not the capacity. She will have need of a good digestive apparatus when through it she has to furnish food for eight or twelve pigs for from five to twelve weeks. The place where the grain is fed to the sows should be dry and exceedingly clean as it is conducive to good health and pigs are clean animals if you will give them a chance to be such. The dust on the feeding floor is injurious to their lings and by or with dust a great many disease germs are transmitted. The sow should have plenty of clean water to drink and slop at meal time. The trough should never be allowed to become sour.
Selection, care and feeding of the brood sow
Citation: Fields, James William. The brood sow. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Feeding of Nursing Mothers; Grains for Brood Sows; Pasture of Brood Sow; Theses